The Skin in Cowden Syndrome - Lim, Agnes; Ngeow, Joanne (Frontiers in Medicine, 2021)
Cowden syndrome (CS) is an autosomal dominant condition caused by mutations in the phosphatase and tensin homolog (PTEN) gene, and is characterized by multiple hamartomas and a predisposition to malignant tumors. Characteristic skin lesions include trichilemmomas, acral keratosis, mucocutaneous neuromas, oral papillomas, and penile macules, and are often the first clues to the underlying diagnosis. Here, we discuss the mucocutaneous manifestations of CS, differential diagnoses of genetic causes of each cutaneous finding, genetic analyses for patients with skin manifestations, management of patients with CS, and potential new targeted therapies for CS.